Correlation between Accelerometer and Questionnaire-Based Assessment of Physical Activity in Patients with Cerebral Palsy - Kwon, Ki Bum; Choi, Young; Sung, Ki Hyuk; Chung, Chin Youb; Lee, Kyoung Min; Kwon, Soon-Sun; Cho, Gyeong Hee; Park, Moon Seok (Clinics in orthopedic surgery, 2020)
Precise measuring and monitoring of physical activity (PA) in patients with cerebral palsy (CP) are critical for assessing their PA participation and its potential health benefits. Accelerometer-based assessment of PA has been considered valid, reliable, and practical in children with CP. Therefore, we investigated the correlation between accelerometer- and questionnaire-based assessment of PA in CP patients. Nineteen patients with CP who were classified as Gross Motor Function Classification System level I-III and 84 normally developed participants were included in the study. Study participants wore an accelerometer for seven days, after which they visited the hospital and completed the International Physical Activity Questionnaire (IPAQ). CP patients and their caregivers completed the Pediatric Outcomes Data Collection Instrument (PODCI) and the Caregiver Priorities and Child Health Index of Life with Disabilities, respectively. The concurrent validity of the questionnaires was assessed. In the accelerometer-based assessment, time spent in PA was significantly shorter at every intensity level in CP patients than in normally developed participants. However, PA assessed by the IPAQ was significantly higher in patients with CP, indicating that they tend to exaggerate their participation in PA. On the correlation of the assessment by the accelerometer and by the PODCI, transfer/basic mobility, sports/physical function, and happiness increased significantly as the number of steps taken and the distance travelled increased. In patients with CP, happiness and quality of life are associated with higher levels of PA. Thus, programs for patients with CP should focus on improving their PA.